Publications from CTA [4] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Ethnoveterinary medicine in Kenya: a field manual of traditional animal health care practices 1996 ISBN 9966 9606 2 7 published by Intermediate Technology Kenya and the International Institute of Rural Reconstruction, Kenya (available from CTA)